Neonatal varicella. A case report. - Patrizi, A.; Rinaldi, R.; Savoia, F.; Neri, I.; Bardazzi, F. (European Journal of Pediatric Dermatology, 2004)
Neonatal varicella is a rare disease, because 90-95% of women have developed specific antibodies against the varicella-zoster virus (VZV) by the time they enter childbearing age (2, 7). The term neonatal varicella refers to a chickenpox that occurs in the first 2 weeks of life in the newborn and during the last 3 weeks of pregnancy or within the first 10 days after delivery in the mother (4). We report here the case of a newborn, who presented neonatal varicella on his second day of life.